La Cité paysanne de Marckolsheim (1940–1944). Étude et protection d’un quartier de fermes modèles en Alsace - Clémentine Albertoni; Laurine Sandoval; Séverine Wodli (In Situ)
In 2008, the Conservation Régionale des Monuments Historiques d’Alsace (Regional Centre for Heritage Conservation in Alsace) launched a thematic survey on the architectural heritage of reconstruction in Alsace, undertaken by the Germans between 1940 and 1944. It started with the study and interpretation of the Cité Paysanne ("peasant settlement") district. This series of fourteen “ideal farms” is remarkable in several ways: its exemplarity and its publicity at the time, the extent of the documentation concerning it, as well as its urban and architectural preservation. This ensemble bears witness to the political will bring about a radical transformation of rural society and the agricultural economy by introducing modernity and renewing the social hierarchy. Furthermore, in considering the nature of this ensemble and the historical context of its construction, this survey led us to think anew about the notion of cultural heritage as well as the procedures which exist for its conservation as historical monuments.